2018
DOI: 10.1021/acs.jpcb.7b12100
|View full text |Cite
|
Sign up to set email alerts
|

Repair Activity of trans-Resveratrol toward 2′-Deoxyguanosine Radicals

Abstract: In the present study, the repair activity of trans-resveratrol toward 2'-deoxyguanosine (dGuo) radicals in polar and nonpolar solvents was studied using density functional theory. The hydrogen transfer/proton coupled electron transfer and single electron transfer (SET) mechanisms between trans-resveratrol and dGuo-radicals were considered. Taking into consideration the molar fraction of neutral trans-resveratrol (ROH) and anionic trans-resveratrol (RO), the overall rate constants for repairing dGuo-radicals by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Resveratrol and other hydroxylstilbenes with 4′‐OH group exhibited lower toxicity, and their radicals have semiquinone structures and are very stable. In a recent work from our group, we studied the repair activity of trans ‐resveratrol toward 2′‐deoxyguanosine radicals and found that trans ‐resveratrol could repair base radicals rather than 2′‐deoxyribose radicals and the repair activity of trans ‐resveratrol anion toward 2′‐deoxyguanosine radicals is better than that of neutral trans ‐resveratrol. However, detail kinetic data for the reactions involved in repairing oxidizing DNA base‐OH‐adduct radicals by hydroxyl‐ trans ‐stilbenes have not been reported until now.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Resveratrol and other hydroxylstilbenes with 4′‐OH group exhibited lower toxicity, and their radicals have semiquinone structures and are very stable. In a recent work from our group, we studied the repair activity of trans ‐resveratrol toward 2′‐deoxyguanosine radicals and found that trans ‐resveratrol could repair base radicals rather than 2′‐deoxyribose radicals and the repair activity of trans ‐resveratrol anion toward 2′‐deoxyguanosine radicals is better than that of neutral trans ‐resveratrol. However, detail kinetic data for the reactions involved in repairing oxidizing DNA base‐OH‐adduct radicals by hydroxyl‐ trans ‐stilbenes have not been reported until now.…”
Section: Introductionmentioning
confidence: 99%
“…Gibbs free energy G was calculated as following equation: G = E HF + G 0 , where E HF represents the total calculated electronic energy at the M06‐2X / ma‐TZVP // 6–311G (d, p) level and G 0 is the thermal correction to Gibbs free energy at the M06‐2X / 6–311G (d, p) level. The method used for calculating Gibbs free energy in this study has been applied in the literature ,,…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation